Waging War against the Woman’s Body: Limitations of the Laws of Armed Conflict and Post-War Justice mechanisms - Latif, Hannah Jasterini (Kent Law Review, 2017)
The following work shall critique the bodies of the laws of armed conflict and international criminal law for their inadequacy in addressing sexual assault during wartime through inappropriate measures to define, incorporate, and progressively interpret international statute to encompass sexual assault as a global crime. In order to illustrate this point one provides a socio-historic examination of the international legal development of sexual assault and an analysis of what makes it a ‘gendered’ crime. The second section shall then critically assess attempts to prohibit sexual assault in the Geneva Conventions, and how its recognition and prosecution under ‘grave breaches’ can be problematic. The third section then examines the decisions made at the ICTY and ICTR to define rape under “greater” crimes such as genocide and crimes against humanity. The overall evaluation of the above shall provide a socio-legal account of the woman’s subordinate and decentralized status in international law by revealing its weaknesses in offering her protection against such a pervasive and heinous crime.